A study on Moodle's performance - Coelho, José (2011)
Learning Management Systems (LMS) are essential tools to the modern teaching institutions. Moodle is an open source LMS, widely used by open and distance teaching universities, as well as support to face to face courses. There are almost 40,000 registered Moodle sites, all over the world. Moodle can be installed in a wide range of environments: operating systems (Linux, Windows), supporting databases (MySQL, PostgreSQL, ...), and hardware. This paper addresses the issue of Moodle’s performance within different environments, and under different loads. What is worth changing and what isn’t to improve performance? When load increases, what should be changed in order to obtain the largest performance gain? To answer these questions, it is important to subject the application, in a test environment, to the real conditions of use. In order to do it, we use historical data on the use of Moodle in Universidade Aberta. Several Moodle instances will be subject to different load levels and the resulting performance will be measured. It is difficult to estimate instantaneous load, even in a working site, where users’ habits are known. The number of users is an easier question to address and may be estimated by the number of teachers and students that will be using the LMS. So, in order to estimate future load, we present a conversion method according to the present level of use in this university.